Linzagolix with and without hormonal add-back therapy for the treatment of symptomatic uterine fibroids: two randomised, placebo-controlled, phase 3 trials. Issue 10356 (17th September 2022) - Donnez, Jacques; Taylor, Hugh S; Stewart, Elizabeth A; Bradley, Linda; Marsh, Erica; Archer, David; Al-Hendy, Ayman; Petraglia, Felice; Watts, Nelson; Gotteland, Jean-Pierre; Bestel, Elke; Terrill, Paul; et al.
Summary: Background: Uterine fibroids are common non-cancerous neoplasm that cause heavy menstrual bleeding and other signs. Linzagolix is an oral gonadotropin-releasing hormone receptor antagonist taken once per day that dose-dependently suppresses gonadal steroids and might reduce uterine-fibroid-associated signs. Two phase 3 trials were conducted to confirm the efficacy and safety of linzagolix at full-suppression (200 mg) and partial-suppression (100 mg) doses with or without hormonal add-back therapy (1 mg oestradiol and 0·5 mg norethisterone acetate) compared with placebo for the treatment of symptomatic uterine fibroids. Methods: PRIMROSE 1 and PRIMROSE 2 were identical 52-week, randomised, parallel, double-blind, placebo-controlled, phase 3 trials conducted at clinics in the USA (PRIMROSE 1) and Europe and the USA (PRIMROSE 2). Eligible women with uterine fibroid-associated heavy menstrual bleeding (menstrual blood loss >80 mL per cycle) were randomly assigned in a 1:1:1:1:1 ratio to one of five masked treatments: (1) placebo, (2) 100 mg linzagolix per day alone, (3) 100 mg linzagolix per day with once-per-day hormonal add-back therapy (1 mg oestradiol and 0·5 mg norethisterone acetate), (4) 200 mg linzagolix per day alone, or (5) 200 mg linzagolix per day with once-per-day hormonal add-back therapy (1 mg oestradiol and 0·5 mg norethisterone acetate). The primary endpoint was a response (menstrual blood loss ≤80 mL and ≥50% reduction from baseline) at 24 weeks in women who received at least one dose of treatment and did not meet any exclusion criteria based on predosing assessments. These trials are registered with ClinicalTrials.gov (NCT03070899 and NCT03070951 ). The trials have been completed. Findings: Between May, 2017, and October, 2020, in PRIMROSE 1, 574 women were enrolled, of which 48 discontinued and 15 were excluded; therefore, 511 women were included in the full analysis set; and in PRIMROSE 2, 535 women were enrolled, of which 24 did not receive the study drug and ten women were excluded from the study, resulting in 501 women being included in the full analysis set. In both trials, a significantly higher proportion of women had a reduction in heavy menstrual bleeding in all linzagolix (with or without add-back therapy) treatment groups compared with the placebo group (p≤0·003). In PRIMROSE 1, the response rates were 56·4% (95% CI 45·8–66·6%) in the 100 mg group, 66·4% (56·6–75·2%) in the 100 mg plus add-back therapy group, 71·4% (61·8–79·8%) in the 200 mg group, and 75·5% (66·0–83·5%) in the 200 mg plus add-back therapy group, compared with 35·0% (25·8–45·0%) in the placebo group. In PRIMROSE 2, the response rates were 56·7% (46·3–66·7%) in the 100 mg group, 77·2% (67·8–85·0%) in the 100 mg plus add-back therapy group, 77·7% (68·4–85·3%) in the 200 mg group, and 93·9% (87·1–97·7%) in the 200 mg plus add-back therapy group, compared with 29·4% (20·8–39·3%) with placebo. The most common adverse events up to 24 weeks were hot flushes (35% of participants in PRIMROSE 1 and 32% in PRIMROSE 2 with linzagolix [200 mg] alone and 3–14% in all other groups). Interpretation: Linzagolix (100 mg or 200 mg) with or without add-back therapy significantly reduced heavy menstrual bleeding. Partial suppression with once-per-day linzagolix (100 mg) without add-back therapy potentially provides a unique option for the chronic treatment of symptomatic uterine fibroids in women who cannot or do not want to take concomitant hormonal add-back therapy. Funding: ObsEva.